Analisis Peran Pihak-Pihak dalam Penegakan Hukum Jinayah Berdasarkan Qanun Aceh Nomor 6 Tahun 2014 - Anisa Nurfazriati; Auliya Rizky Sulistiani; Allian Sadira; Deden Najmudin (Postmodernism: Indonesian Journal of Multidisciplinary Islamic Studies, 2026)
This study analyzes the complexities of enforcing Jinayah Law in Aceh under Qanun Aceh Number 6 of 2014, focusing on the effectiveness of its multi-stakeholder ecosystem. Using a descriptive-analytical qualitative approach through library research, this study reveals that despite a clear legal foundation, the implementation faces significant challenges of systemic fragmentation. Wilayatul Hisbah (WH), as the frontline enforcement agency, is constrained by structural issues such as limited human resource capacity and budget. The Syar'iyah Court navigates the dynamic of balancing substantive Islamic law with modern procedural justice. Furthermore, synergy with traditional institutions (Mukim and Gampong) and coordination with national law enforcement agencies like the police remain suboptimal, often leading to dualism in case handling. The findings indicate that the core problem lies not in the legal norms but in the weak synergy and coordination among all stakeholders. Systemic challenges, including inconsistent political and budgetary support, coupled with the absence of a comprehensive monitoring and evaluation mechanism, further undermine enforcement effectiveness. Therefore, this study recommends establishing an integrated synergy model, such as a Syar'iyah Justice Hub, as a permanent coordinating body to develop standard protocols, conduct cross-institutional training, and perform periodic evaluations. Strengthening this integrated law enforcement ecosystem is crucial for achieving the substantive goal of Jinayah Law: realizing community well-being (maslahah) as intended by the maqasid al-shariah (the higher objectives of Islamic law)